Case Report: A 1-year progression of mediolateral gait instability during tandem walking in FXTAS - Lee-Confer, Jonathan; Baker, Dian; Hagerman, Randi; Maltman, Nell; Kobel, Megan; Imamura, Rodney (Frontiers in Sports and Active Living, 2025)
Fragile X-associated Tremor/Ataxia Syndrome (FXTAS) is a late-onset neurodegenerative disorder characterized by progressive motor dysfunction, including cerebellar ataxia and gait instability. Although tandem walking is a sensitive clinical marker of cerebellar dysfunction, its utility in tracking longitudinal motor decline in FXTAS remains unexplored and the trajectory of motor decline in FXTAS is not well characterized. Therefore, the purpose of this case report was to determine whether tandem walking performance deteriorates over a one-year period in an individual with FXTAS. A 68-year-old male with genetically confirmed FXTAS completed a 15-second tandem walking trial at baseline and again after one year. Kinematic data were collected using a Vicon motion capture system. Step width was calculated at each heel strike as the distance between the mediolateral position of the left and right heel markers. The mean step width considerably increased from baseline tandem walking of 45.21 ± 33.47 mm (SD) compared to the 1-year follow-up trial step width of 85.79 ± 15.80 mm (SD) indicating potential progressive mediolateral instability. This case report provides preliminary evidence that step width during tandem walking may be a sensitive marker of longitudinal motor decline in FXTAS and declines in gait stability can occur within one year. Larger studies with repeated measures and additional gait metrics are warranted to validate these findings.